Investigation of the mechanisms for stable superlubricity of poly(vinylphosphonic acid) (PVPA) coatings affected by lubricant - Caixia Zhang; Zhifeng Liu; Yuhong Liu; Qiang Cheng; Congbin Yang; Ligang Cai (Friction)
Abstract The stability of the tribological properties of polymer coatings is vital to ensure their long term use. The superlubricity of the poly(vinylphosphonic acid) (PVPA)-modified Ti6Al4V/polytetrafluoroethylene (PTFE) interface can be obtained when lubricated by phosphate-buffered saline (PBS, pH = 7.2), but not when lubricated by deionized water and ethanol. Therefore, the mechanisms for the superlubricity of PVPA coatings affected by lubricant were investigated in detail. The stability of the PVPA coatings and their compatibility with the lubricant are critical factors in realizing ideal tribological properties of PVPA coatings. Robust PVPA coatings are stable under a wide range of pH values (6–10) using PBS as the basic solution, and are also characterized by superlubricity. The hydrolysis kinetics of phosphate anhydride is the main reason for the pH responses. In addition, along with stability, PVPA coatings exhibit different friction coefficients in salt solutions which are composed of various ions, which indicates that the compatibility between PVPA coatings and the lubricant can be used to regulate the superlubricity properties. Based on a fundamental understanding of the mechanism of surperlubricity by considering the effects of the lubricant, PVPA coatings with stability and perfect tribological performance are expected to be applied in more aspects.